Pharmacogenetics in type 2 diabetes: influence on response to oral hypoglycemic agents - Dawed AY; Zhou K; Pearson ER (Dove Medical Press, 2016)
Adem Yesuf Dawed, Kaixin Zhou, Ewan Robert Pearson  Division of Cardiovascular and Diabetes Medicine, Medical Research Institute, University of Dundee, Dundee, Scotland, UK Abstract: Type 2 diabetes is one of the leading causes of morbidity and mortality, consuming a significant proportion of public health spending. Oral hypoglycemic agents (OHAs) are the frontline treatment approaches after lifestyle changes. However, huge interindividual variation in response to OHAs results in unnecessary treatment failure. In addition to nongenetic factors, genetic factors are thought to contribute to much of such variability, highlighting the importance of the potential of pharmacogenetics to improve therapeutic outcome. Despite the presence of conflicting results, significant progress has been made in an effort to identify the genetic markers associated with pharmacokinetics, pharmacodynamics, and ultimately therapeutic response and/or adverse outcomes to OHAs. As such, this article presents a comprehensive review of current knowledge on pharmacogenetics of OHAs and provides insights into knowledge gaps and future directions. Keywords: pharmacogenetics, type 2 diabetes, oral hypoglycemic agents, pharmacokinetics, pharmacodynamics, response